Processing of Your Banana Peel Waste (Mussa paradisiaca) into Organic Vinegar with the Addition of Acetobacter aceti bacteria - Armi Armi; Husainah Husainah; Desi Sri Pasca Sari Sembiring; Roslina Roslina; Elvitriana Elvitriana (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the process of processing Awak banana peel waste (Musa paradisiaca) into organic vinegar by giving Acetobacter aceti bacteria and to determine the use of Acetobacter aceti bacteria to affect the processing of Awak banana peel waste into organic vinegar. This research was conducted from September to October 2022 at LAB MIPA USM, Banda Aceh. The method used in this study is a complete randomized design (RAL) with a 1 factorial pattern, namely the addition of Acetobacter aceti bacteria (P0=0%, P1=10%, P2=20%, P3=30% and P4=40%). Based on the results of the study, it shows a good treatment obtained at P1, namely with the addition of Acetobacter aceti bacteria as much as 10%. While the lowest results were obtained in P0 treatment without the addition of Acetobacter aceti bacteria. The results of the ANAVA test on vinegar color, vinegar taste, vinegar aroma and vinegar PH showed a real difference and the results of research on the amount of acetic acid obtained were (P0 = 0.6%, P1 = 6%, P2 = 4.8%, P3 = 4.2%, P4 = 3%). Then your banana peel waste can be used as a basic ingredient for making organic vinegar and Acetobacter aceti bacteria have a positive effect on processing your banana peel waste into organic vinegar.